Development and Evaluation of a Tethered Class C3 Hexacopter in Maritime Conditions on the Helipad of a Ferry - Cezary Kownacki; Leszek Ambroziak; Maciej Ciężkowski; Adam Wolniakowski; Sławomir Romaniuk; Zbigniew Kulesza; Arkadiusz Bożko; Daniel Ołdziej (Applied Sciences, 2023)
Various unmanned aerial vechicle (UAV) applications, especially those based on reconnaissance and observation missions, often require an unlimited time of flight. This is possible only when a UAV is continuously supplied with power from a ground-based power source, which is why tethered UAV systems were developed. Tethered UAV systems are based on multicopters, which can hover above a landing pad or track its position if it is movable. The presented research concerned the development of a large C3 class hexacopter with a maximal payload of about 1 kg and a takeoff mass of 16 kg, which was tested in maritime conditions during a ferry’s cruise. The main purpose of the hexacopter was to continuously observe the area ahead of the vessel to detect and localize obstacles in the water. During the experimental tests, critical phases of flight were identified, the AC/DC power supply unit and power cord unwinder were tested, and the power required by six brushless direct current (BLDC) motors was registered. The obtained results could be useful in future work on tethered UAV systems applied in windy maritime conditions.